Why Should One Choose Pharmacy as a Career? (Asian Journal of Pharmaceutics (AJP), 2015)
Objective of this article is to motivate the disheartened pharmacy professional toward profession through giving thorough knowledge of opportunities in pharmacy field. Although job opportunities for pharmaceutical professionals are with private as well as government sector but in these studies is mainly to point out the career opportunity of pharmaceutical professionals in department wise in private as well as government sector. At the commencement, the article gives a picture of the draft of enormous and growing industry. This study also reflects the all requirement for pharmacy professional doing job in various departments. Inside the pharmaceutical industry, pharmacy professional might be involved in various activities relating to the discovery, development, action, safety, formulation, production, quality control, quality assurance, packaging, storage, marketing, clinical research, legal advisor, documentation and technology transfer etc. There is ample scope of research for the pharmacy professional in India and abroad. Knowledge Process Outsourcing and Business Process Outsourcing, Bio-Informatics and Medical Transcription are the new options for job opportunity and career advancement for the pharmaceutical professionals. There is an enormous career opportunity for pharmaceutical professionals in the pharmaceutical industry but only those which are having progressive attitude and confidence.